Regional Absorption of Terms of Trade Shocks - Eduardo Haddad; Fernando Perobelli (European Regional Science Association (ERSA), 2001)
As the process of global integration evolves, developing economies become more and more dependent upon the swings of international markets. Changes in the external environment and economic policy have played a major role in determining the performance of these economies. Terms of trade shocks represent one of the most important issues related to recent developments in low and middle income countries, whose effects have been widely studied in the economic literature. However, attention has always been focused on the national economies, without any consideration of the ability of these economies to absorb these shocks through interregional interactions. In this paper we address this issue using an bottom-up interregional CGE model. It is shown that the degree of integration of the national economies helps to absorb external shocks, decreasing the adverse impacts of negative terms of trade shocks as the economy becomes more integrated.
Keywords: 330